The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/17479541231164090
|View full text |Cite
|
Sign up to set email alerts
|

Additional substitutions in elite European football

Abstract: In 2020, the International Football Association Board (IFAB) introduced a temporary rule amendment of two additional substitutions in regular time. In this study, we assess the impact of this rule change with regard to player relief, tactical influence by the coaches and the development of young players. Data were collected from 3652 matches from the top 5 leagues in the Union of European Football Associations (UEFA) rankings and 659 UEFA club competition matches (Champions League and Europa League) in 2 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This means that the 5-subsitution rule may lead to a higher overall running performance [ 19 , 32 ], but this change is related to the number as well as the type of substitutions being made [ 20 ]. In addition, coaches may use substitutions to reduce the load of team [ 18 , 21 ], which is extremely important to maintain the physical condition of the whole team in the World Cup with a congested schedule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the 5-subsitution rule may lead to a higher overall running performance [ 19 , 32 ], but this change is related to the number as well as the type of substitutions being made [ 20 ]. In addition, coaches may use substitutions to reduce the load of team [ 18 , 21 ], which is extremely important to maintain the physical condition of the whole team in the World Cup with a congested schedule.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the substitutes come on to the pitch with a greater running intensity, their overall game load is considerably lower than that of the starters due to the lower playing time [ 16 , 17 ]. More recently, studies have shown that teams under the new substitution rule have an overall increase in running performance while the team load and RPE decrease [ 18 21 ], which is especially important during congested fixtures [ 22 ], indicating the importance of using multiple substitutions. In fact, the data from the 2022 World Cup shows that there was no reduction in high-intensity running by teams in the second half [ 23 ], in contrast to the results from previous World Cups [ 24 ].…”
Section: Introductionmentioning
confidence: 99%